Five advantages of skill. (January 2018) - Patchett, Merle; Mann, Joanna
In this Special Issue we explore and extend conceptions, characterisations, and applications of skill within and beyond geography. Framed by the question: "where is skill located?", the papers assembled do not just explore where skilled practice 'takes place', its sites and situations, but also prompt a deeper ontological and epistemological rethinking of skill. And it is this rethinking of skill that is at stake in our editorial. In what follows, we map out this rethinking and introduce the five advantages of skill that the papers develop. Firstly, skill is practical in that it is concerned with the actual doing or use of something with accomplishment. Secondly, skill is processual in that the skilled practitioner works emergently and responsively rather than rubrically and successionally. Thirdly, skill is technical in that it involves not just techniques of the body but encompasses what Bernard Stiegler calls the 'originary technicity' of the body. Fourthly, skill is ecological in that it is not of the individual body, but of the entire field of relations that make practice possible. And finally, skill is political in that there is a continuous flow between the micro – (that which is emergent) and macro – (that which exists more concretely and can be represented) politics of practice.